Multi-dimensional couple bargaining and housework allocation - Gøsta Esping-Andersen; Christian Schmitt (Acta Sociologica, 2020)
Research on couple bargaining and housework allocation focuses almost exclusively on partners' economic resources. In this study, we ask whether additional bargaining resources, namely physical appearance and social networks, may exert a distinct effect – that is, whether partners can mobilize multiple resources within their bargaining framework. A focus on multiple bargaining chips is made possible by the German Socio-Economic Panel Study. In line with previous research, we conclude that earnings potential is the most important bargaining chip. But we also find that physical attractiveness can make a significant difference, although its effects depend on age. We uncover no distinct effects for social networks.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer bundesweiten Konsortiallizenz in der Nachfolge einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich.
Keywords: 330; Housework; Couple bargaining; Bargaining power; Earnings potential; Attractiveness; Social networks